Endothelial dysfunction and abnormal vascular structure are simultaneously present in patients with heart failure with preserved ejection fraction. (15th March 2017) - Kishimoto, Shinji; Kajikawa, Masato; Maruhashi, Tatsuya; Iwamoto, Yumiko; Matsumoto, Takeshi; Iwamoto, Akimichi; Oda, Nozomu; Matsui, Shogo; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; Goto, Chikara; et al.
Abstract: Background: Endothelial dysfunction and abnormal vascular structure may be involved in the pathogenesis of chronic heart failure (HF). The purpose of this study was to evaluate simultaneously vascular function and vascular structure in patients with heart failure with preserved ejection fraction (HFpEF). Methods: We measured flow-mediated vasodilatation (FMD) and nitroglycerine-induced vasodilation as indices of vascular function and intima-media thickness (IMT) as an index of vascular structure of the brachial artery in 41 patients with HFpEF (23 men and 18 women; mean age, 66 ± 12 yr) and 165 patients without HF (95 men and 70 women; mean age, 54 ± 16 yr). Results: FMD was significantly smaller in patients with HFpEF than in patients without HF (2.9 ± 2.1% versus 4.6 ± 2.7%, P = 0.0002). Nitroglycerine-induced vasodilation was significantly smaller in patients with HFpEF than in patients without HF (9.3 ± 4.1% versus 12.9 ± 4.9%, P < 0.0001). Brachial artery IMT was significantly larger in patients with HFpEF than in patients without HF (0.35 ± 0.06 mm versus 0.31 ± 0.07 mm, P = 0.0002). After adjustment for age, sex, hypertension, dyslipidemia, and diabetes mellitus, the associations remained significant between HFpEF and FMD (odds ratio, 0.79; 95% confidence interval, 0.66–0.92; P = 0.0032), nitroglycerine-induced vasodilation (odds ratio, 0.88; 95% confidence interval, 0.80–0.96; P = 0.0039), and brachial artery IMT (odds ratio, 1.08; 95% confidence interval, 1.01–1.17; P = 0.033). Conclusions: These findings suggest that both endothelial dysfunction and abnormal vascular structure may contribute to the pathogenesis and maintenance of HFpEF. Endothelial function and vascular structure may be potential therapeutic targets for HFpEF.